Immunophenotyping of amelanotic melanoma - Lazarević, Viktor (Acta dermatovenerologica Alpina, Pannonica et Adriatica, 2006)
Amelanotic malignant melanoma (AMM) is a subtype of cutaneous melanoma with little or no pigment upon visual inspection. The lack of pigmentation is the reason for late diagnosis of lesions and a poor prognosis. We report a case ofa 55-year-old female with an AMM diagnosed by immunophenotyping. Monoclonal antibodies S-100, HMB-45, and antibodies to cytokeratin were used. Our patientunderwent a wide local excision (a 2 cm wide margin) 2 years ago. So far there are no signs of a recurrence. In doubtful cases, immunophenotyping with monoclonal antibodies HMB-45 and S-100 is important for confirming the correct diagnosis of AMM.
Keywords: Antibodies, Monoclonal; Diagnosis; diagnostika; genetics; genetika; Immunophenotyping; Imunofenotipizacija; kožne bolezni; melanom; Melanom amelanotični; Melanoma, Amelanotic; Protitelesa monoklonska